2022
DOI: 10.1039/d2ta05186a
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an all zero-dimensional CsPbBr3/CdSe heterojunction for highly efficient photocatalytic CO2reduction

Abstract: Metal halide perovskite quantum dots (QDs) are regarded as one of the promising photocatalysts for CO2 reduction because of their unique optoelectronic properties. However, the severe charge recombination and insufficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…[3,4] As an emerging candidate photocatalyst, perovskite nanocrystals (PNCs) have attracted enormous Recently, the PNC-chalcogenide heterojunctions, like CsPbBr 3 / CdS core/shell, CsPbBr 3 -PbS, CsPbBr 3 -CdSe, and CsPbBr 3 -PbSe, have been developed for photocatalysis. [26][27][28][29] However, the direct growth of PNCs on metal chalcogenide have not yet been well-established.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] As an emerging candidate photocatalyst, perovskite nanocrystals (PNCs) have attracted enormous Recently, the PNC-chalcogenide heterojunctions, like CsPbBr 3 / CdS core/shell, CsPbBr 3 -PbS, CsPbBr 3 -CdSe, and CsPbBr 3 -PbSe, have been developed for photocatalysis. [26][27][28][29] However, the direct growth of PNCs on metal chalcogenide have not yet been well-established.…”
Section: Introductionmentioning
confidence: 99%
“…The shorter lifetime of the Z-scheme heterostructure is strongly attributed to the existence of more efficient non-radiative decay pathways in the composites, which was caused by the electron transfer from WO 3 to Tp–TAPB. 52,53 Therefore, WO 3 /Tp–TAPB shows an excellent photocatalytic H 2 O 2 production performance. A rotating ring-disk electrode (RRDE) was used to determine the selectivity of the catalyst toward the production of H 2 O 2 instead of H 2 O and the calculated selectivity is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…20 Gong's group synthesized a 0D/0D type-II CsPbBr 3 /CdSe heterojunction by an in situ growth method. 105 DFT calculations showed that there was a strong electronic coupling of Pb-Se and Br-Cd bonds, which facilitated fast electron transfer and separation. In situ diffuse reectance infrared Fourier transform spectroscopy (DRIFTS) found that the intermediate Cd-C 2 O 4 − adduct could enable efficient CO 2 activation and accelerate CO production.…”
Section: Heterojunction Constructionmentioning
confidence: 99%